Pengaruh Nilai Tukar Rupiah, Harga Internasional Kakao dan Jumlah Produksi Kakao Terhadap Volume Ekspor Kakao: Penelitian - Intan Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the influence of the rupiah exchange rate, international cocoa prices, and cocoa production volume on Indonesia's cocoa export volume from 2004 to 2023. This research employs a quantitative method using secondary time series data sourced from the Central Statistics Agency (BPS), Bank Indonesia, and the International Cocoa Organization (ICCO). The analysis method used is the Error Correction Model (ECM), preceded by stationarity and cointegration tests. The results indicate that in the long term, the rupiah exchange rate has a negative and significant effect on cocoa export volume (t-statistic –2.174528; prob. 0.0450), while international cocoa prices (t-statistic 0.687522; prob. 0.0016) and cocoa production volume (t-statistic 2.594265; prob. 0.0196) have a positive and significant effect. In the short term, the rupiah exchange rate has a negative effect, while international cocoa prices and cocoa production have a positive effect on export volume. Simultaneously, all three variables significantly influence cocoa export volume with an F-statistic of 7.964367 (long term) and 3.121247 (short term). The coefficient of determination (R²) is 59.89% in the long term and 47.13% in the short term, indicating that the rupiah exchange rate, international cocoa prices, and cocoa production volume can explain variations in Indonesia's cocoa export volume.